Profile of science outreach actions at the University for International Integration Of The Afro-Brazilian Lusophony (UNILAB) between 2014 and 2022 (Citizenship in Action: Extension and Culture Magazine, 2024)
We present, in this paper, the profile of science outreach action developed at the University for International Integration of the Afro-Brazilian Lusophony (UNILAB). We analyzed qualitative and quantitative data provided by the institution’s Science Outreach, Arts and Culture Dean’s Office (PROEX), via two documents published in 2021 and 2022. Therefore, we point out the important parameters and references to science outreach in Brazil, contextualizing the analysis within a perspective of social and academic relevance, potentialities and challenges experienced by science outreach in Brazilian higher education institutions, within the current context. Next, we present and analyze the science outreach actions, taking into consideration thematic areas, registered and executed actions, relationships with academic units, with agents from civil society and politics and with the objectives of sustainable development, forms of registration and assessment and demands pointed out by the projects. Finally, we present the main synthetic-analytical results generated.
Keywords: science outreach; university; higher education